Germ plasm-related structures in marine medaka gametogenesis; novel sites of Vasa localization and the unique mechanism of germ plasm granule arising. Issue 1 (8th October 2019) - Reunov, Arkadiy A.; Au, Doris W. T.; Alexandrova, Yana N.; Chiang, Michael W. L.; Wan, Miles T.; Yakovlev, Konstantin V.; Reunova, Yulia A.; Komkova, Alina V.; Cheung, Napo K. M.; Peterson, Drew R.; Adrianov, Andrey V.
Summary: Germ plasm, a cytoplasmic factor of germline cell differentiation, is suggested to be a perspective tool for in vitro meiotic differentiation. To discriminate between the: (1) germ plasm-related structures (GPRS) involved in meiosis triggering; and (2) GPRS involved in the germ plasm storage phase, we investigated gametogenesis in the marine medaka Oryzias melastigma . The GPRS of the mitosis-to-meiosis period are similar in males and females. In both sexes, five events typically occur: (1) turning of the primary Vasa-positive germ plasm granules into the Vasa-positive intermitochondrial cement (IMC); (2) aggregation of some mitochondria by IMC followed by arising of mitochondrial clusters; (3) intramitochondrial localization of IMC-originated Vasa; followed by (4) mitochondrial cluster degradation; and (5) intranuclear localization of Vasa followed by this protein entering the nuclei (gonial cells) and synaptonemal complexes (zygotene–pachytene meiotic cells). In post-zygotene/pachytene gametogenesis, the GPRS are sex specific; the Vasa-positive chromatoid bodies are found during spermatogenesis, but oogenesis is characterized by secondary arising of Vasa-positive germ plasm granules followed by secondary formation and degradation of mitochondrial clusters. A complex type of germ plasm generation, 'the follicle cell assigned germ plasm formation', was found in late oogenesis. The mechanisms discovered are recommended to be taken into account for possible reconstruction of those under in vitro conditions.